2019
DOI: 10.1021/acs.jpcb.9b07732
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism Study of Bacteria Killed on Nanostructures

Abstract: It is important to study the bactericidal mechanism with nanostructures for the design and preparation of high-efficiency sterilization materials. In this paper, the interfacial energy gradient between cells and nanopillars is proposed to be the driving force to promote cells to migrate into nanostructures and get killed. The expressions of interfacial energy and its gradient were first established, then the deformation of cells pressured by nanostructures was calculated. The results show that the interfacial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 64 publications
0
37
0
Order By: Relevance
“…[ 46 ] Here, we focus on the interactions with S. aureus (Gram‐positive—highly rigid and thus harder to inactivate than Gram‐negative species), [ 46 ] and for guidance, calculate the pressure exerted on cells by various topographies (Figures S21 and S22, Supporting Information). [ 47 ] The data confirm a lower tip diameter generates higher pressure exerted on the cell, with pitch being inversely proportional (Figure S22, Supporting Information). For our P100 structures, ( p = 110 nm; d T = 21 nm), the model predicts a pressure of ≈10 MPa indicating that creep deformation can occur with the potential to rupture given sufficient nanopillar height.…”
Section: Resultsmentioning
confidence: 70%
“…[ 46 ] Here, we focus on the interactions with S. aureus (Gram‐positive—highly rigid and thus harder to inactivate than Gram‐negative species), [ 46 ] and for guidance, calculate the pressure exerted on cells by various topographies (Figures S21 and S22, Supporting Information). [ 47 ] The data confirm a lower tip diameter generates higher pressure exerted on the cell, with pitch being inversely proportional (Figure S22, Supporting Information). For our P100 structures, ( p = 110 nm; d T = 21 nm), the model predicts a pressure of ≈10 MPa indicating that creep deformation can occur with the potential to rupture given sufficient nanopillar height.…”
Section: Resultsmentioning
confidence: 70%
“…Furthermore, the model indicated that high-motile bacteria are less resistant to nanopatterned surfaces [57]. Liu et al [58] implemented an investigation into the interfacial energy gradient between the cells and nanopillars, which was proposed as the driving force to promote cell adhesion, and the results implied that nanopillar parameters were a substantial influence factor of the interfacial energy gradient. Higher aspect ratio could exert greater pressure on the cell membrane, while smaller cell volume would be exerted at higher pressure with larger contact angle.…”
Section: Perspectives Of Contemporary Nanostructure-membrane Interactionmentioning
confidence: 99%
“…The investigation of bacteria-nanotopography interactions has, therefore, become a significant research interest for the efficient and effective development of advanced fabricated bactericidal nanotextured surfaces (NTS) for biomaterials application. [5][6][7][8] This is a growing field of research as nanotextured surfaces do not leach bactericidal chemicals, and therefore, the bactericidal property is conserved for longer periods compared to chemical approaches. [9][10] Furthermore, nanotextured surfaces are non-toxic and more effective at controlling bacterial strains that produce extracellular polymeric substance (EPS) secretions.…”
Section: Introductionmentioning
confidence: 99%